Prospective feasibility analysis of a novel off-line approach for MR-guided radiotherapy - Bostel, Tilman; Debus, Jürgen; Huber, Peter E.; Sterzing, Florian; Nicolay, Nils (Strahlentherapie und Onkologie, 2018)
Background: The present work aimed to analyze the feasibility of a shuttle-based MRI-guided radiation therapy (MRgRT) in the treatment of pelvic malignancies. Patients and methods: 20 patients with pelvic malignancies were included in this prospective feasibility analysis. Patients underwent daily MRI in treatment position prior to radiotherapy at the German Cancer Research Center. Positional inaccuracies, time and patient compliance were assessed for the application of off-line MRgRT.ResultsIn 78% of applied radiation fractions, MR imaging for position verification could be performed without problems. Additionally, treatment-related side effects and reduced patient compliance were only responsible for omission of MRI in 9% of radiation fractions. The study workflow took a median time of 61 min (range 47–99 min); duration for radiotherapy alone was 13 min (range 7–26 min). Patient positioning, MR imaging and CT imaging including patient repositioning and the shuttle transfer required median times of 10 min (range 7–14 min), 26 min (range 15–60 min), 5 min (range 3–8 min) and 8 min (range 2–36 min), respectively.To assess feasibility of shuttle-based MRgRT, the reference point coordinates for the x, y and z axis were determined for the MR images and CT obtained prior to the first treatment fraction and correlated with the coordinates of the planning CT. In our dataset, the median positional difference between MR imaging and CT-based imaging based on fiducial matching between MR and CT imaging was equal to or less than 2 mm in all spatial directions. The limited space in the MR scanner influenced patient selection, as the bore of the scanner had to accommodate the immobilization device and the constructed stereotactic frame. Therefore, obese, extremely muscular or very tall patients could not be included in this trial in addition to patients for whom exposure to MRI was generally judged inappropriate. Conclusion: This trial demonstrated for the first time the feasibility and patient compliance of a shuttle-based off-line approach to MRgRT of pelvic malignancies.
Gesehen am 04.04.2019